Turning discontent into votes: Economic inequality and ethnic outbidding - Ronald J McGauvran; Brandon Stewart (Research & Politics)
Ethnic outbidding, where parties adopt ever more extreme positions to capture electoral advantage, has become an increasingly common practice among ethnic parties. As economic issues have often served as a catalyst for ethnic tension, increasing levels of economic inequality should lead parties to adopt more extreme positions in an attempt to outbid one another. Furthermore, as their economic and ethnic platforms will appeal to the same ethnically defined constituency, ethnic outbidding should be more effective where inequality is high. Using a sample of over 150 ethnonational parties in Europe between 2011 and 2017, this paper finds that inequality is linked to increasing ideological extremism along a number of policy dimensions. Employing local-level voting data for Romania and Slovakia, we show that higher inequality makes adopting a more ideological extreme position a more successful electoral strategy, especially where economic issues are ethnically salient.